Pharmacological Values and Phytochemical Properties of Devil’s Cotton (Ulatkambal) - A Review (Bangladesh Pharmaceutical Journal, 2019)
Devil’s cotton (Ulatkambal) is a genus in the family Malvaceae, with one or two species from Asia and Australia. Literature review revealed that Abroma augusta (Devil’s cotton) is widely used in Ayurvedic medicine as a popular drug. Devil’s cotton has been claimed to possess major biological activities like anti-diabetic, analgesic, anti-inflamatory, thrombolytic, antioxidant, hypolipidemic etc. They are also utilized by the traditional local healers of different Asian countries to treat various diseases like diabetes mellitus, as uterine tonic in emmerogogue, dysmenorrhea, amenorrhoea, sterility and other menstrual disorders, rheumatic pains of joints and headache with sinusitis. Biochemical profiling of different parts of the plant demonstrated the presence of some important phytochemicals like alkaloids, abromin, sterol, friedelin, abromasterol, taroxerylacetate, taraxeral and β-sitosterol. The aim of this review was to analyze the published report based on the medicinal values of Devil’s cotton species as well to provide the updated information about the ethnomedicinal, pharmacological as well as the phytochemical properties.Bangladesh Pharmaceutical Journal 22(1): 109-116, 2019